Carbon Deposition and Burial in Estuarine Sediments of the Contiguous United States. Issue 2 (28th January 2020) - Hutchings, J. A.; Bianchi, T. S.; Najjar, R. G.; Herrmann, M.; Kemp, W. M.; Hinson, A. L.; Feagin, R. A.
Abstract: Estuaries represent the primary linkage between the terrestrial and marine carbon cycles, and estuarine processing of riverine and coastal carbon plays a disproportionately large role in the global carbon cycle relative to the small areal extent of the estuarine environments. However, knowledge of the rate of organic carbon deposition and burial in estuarine sediments is lacking at regional scales. Data on surficial total organic carbon, linear sedimentation, and bulk density of estuarine sediments were compiled and categorized via a cluster analysis in order to estimate carbon deposition within the contiguous United States (CONUS). The cluster analysis broadly grouped estuaries by geography, but exceptions to geographic clustering highlighted differences within regions. A transfer function from deposition to burial based on linear sedimentation rate was used to estimate burial efficiency, and thus the rate of carbon burial within each cluster. We estimate organic carbon deposition rates within CONUS estuarine sediments to be 161 [121–217, 95% confidence] g C/m 2 /yr with a burial efficiency estimated at 38 [34–42, 95% confidence] %, which yields a long‐term burial rate of 64 [44–97, 95% confidence] g C/m 2 /yr. Spatially integrated organic deposition and burial rates are 11.3 [8.5–15.2, 95% confidence] and 4.5 [3.1–6.8, 95% confidence] Tg C/yr, respectively. Our findings allow a more thorough understanding of coastal carbon cycling, which is critical for both management purposes as well as for the assessment of the role of estuaries in past and future climate change. Plain Language Summary: Estuaries are diverse ecosystems located at the coastal mouth of rivers or within embayments, where terrestrial and marine environments meet. Estuaries tend to be highly productive and provide many critical ecosystem services for their communities. Carbon‐based material delivered primarily by rivers or produced by aquatic organisms is deposited within the sediments of estuaries. Organisms in sediments consume some of the deposited material and respire it principally as carbon dioxide. However, a portion is buried within deeper sediments and is removed from the contemporary carbon cycle. The rate of material deposited and ultimately buried can influence the function of the estuary as well as its relation to communities and the adjacent coastal ecosystems. On longer time scales (many thousands of years), this removal can also influence the global carbon cycle. We grouped estuaries based on their physical and chemical characteristics and estimated sediment deposition and burial rates for the contiguous United States, where we found that approximately 40% of deposited material was buried within sediments. Key Points: Sedimentation processes in estuaries within the contiguous United States are estimated to deposit 11.3 [8.5–15.2, 95% confidence] Tg of carbon per year Remineralization liberates a significant portion of deposited carbon, yielding centennial‐scale burial of 4.5 [3.1–6.8, 95% confidence] Tg carbon per year Estuaries of the contiguous United States are classified into six clusters based on geospatial and biogeochemical characteristics using k ‐means analysis